Respuesta :

Answer:

Option a. [tex](gof)(3) = -25[/tex]

Step-by-step explanation:

They ask us to find

(gof)(3)

To solve this problem we must introduce the function f(x) within the function g(x)

That is, we must do g(f(x)).

So, we have:

[tex]f(x) = |x + 2|\\\\g(x) = -x^2[/tex]

Then:

[tex]g(f(x)) = -(|x + 2|) ^ 2[/tex]

This is:

[tex]g(f(x)) = -(x + 2) ^ 2[/tex]

Now we must do x = 3

[tex]g(f(3)) = -(3 + 2) ^ 2[/tex]

[tex](gof)(3) = -25.[/tex]

The answer is: [tex](gof)(3) = -25.[/tex]

Answer:

(gof)(3) = -25

Step-by-step explanation:

We have given two functions.

f(x)= |x+2|

g(x)= -x²

We have to find (gof)(3).

(gof)(x) =  ?  and (gof)(3) = ?

(gof)(x) =  g(f(x))

(gof)(x) =   g( |x+2|)

(gof)(x) = -( |x+2|)²

Since, we know that

( |x|)²  = x²

hence, (gof)(x) =  -(x+2)²

Putting x = 3 in above equation, we have

(gof)(3) =-(3+2)²

(gof)(3) = -(5)²

(gof)(3) = -25 which is the answer

ACCESS MORE